Mathematical modeling of Cs+ transport phenomena from solidified spent ion exchange resin - Dimović Slavko D. (VINCA Institute of Nuclear Sciences, 2021)
The aim of the study was to assess Cs+ ions transport phenomena from solidified spent ion exchange resin by mathematical modeling. The experimental results comparison was obtained by Hespe's Standard Leaching Method. For the leaching prediction rate as a function of time, diffusion and semi-empirical models were used. Due to the presence of spent ion exchange resin, the cement matrix absorbed a larger amount of water, swelled, and degraded. This phenomenon caused a significantly lower value of mechanical resistance to pressure. Also, through the increase of bentonite and zeolite content, the cement matrix decreased its mechanical resistance. The retention of cesium ions in the cement matrix was low and they were leached during the early phase of the investigation. The diffusion coefficient, De, decreased by three orders of magnitude with the addition of zeolite and bentonite in the cement matrix. Linear regression of experimental Cs+ leaching results, under static conditions, displayed that the semi-empirical parameter K3 than the absolute values of the parameters K2 and K1. Therefore, the contribution of matrix dissolution to the total radionuclides transport was irrelevant to the prevailing share of diffusion and surface washing processes.